Assessment of Tumor-infiltrating Lymphocytes Predicts the Behavior of Early-stage Oral Tongue Cancer. (October 2019) - Heikkinen, Ilkka; Bello, Ibrahim O.; Wahab, Awais; Hagström, Jaana; Haglund, Caj; Coletta, Ricardo D.; Nieminen, Pentti; Mäkitie, Antti A.; Salo, Tuula; Leivo, Ilmo; Almangush, Alhadi
Abstract : Tumor-infiltrating lymphocytes (TILs) have shown a promising prognostic value in many epithelial cancers. We sought to assess the prognostic value of TILs in a multicenter cohort of early oral tongue squamous cell carcinoma (OTSCC). The percentage of TILs was assessed on the surgical resection slides stained with hematoxylin and eosin. The assessment of TILs was performed in the stromal compartment and in the intraepithelial compartment (at the invasive front and at the center of the tumor). We followed the method that was described recently by the International Immuno-Oncology Biomarker Working Group for the assessment of TILs. A total of 308 cases from the 5 Finnish university hospitals and from A.C. Camargo Cancer Center, São Paulo, Brazil, were included. We found a promising prognostic value for stromal TILs at the invasive front in the multivariable analysis with a hazard ratio of 2.61 (95% confidence interval [CI], 1.77-3.83; P <0.001) for overall survival, 1.99 (95% CI, 1.07-3.69; P =0.040) for disease-specific survival, and 1.94 (95% CI, 1.14-3.29; P =0.020) for disease-free survival. In conclusion, evaluation of TILs is simple and can aid in identifying the high-risk cases of early OTSCC. The method introduced by the International Immuno-Oncology Biomarker Working Group can be used for standardized determination of TILs in early OTSCC.